The relationship between anxiety levels and blood glucose levels in diabetes mellitus patients: A cross-sectional study - Julkarnain, Julkarnain; Arham, Arham; Supriadin, Bobi (Indonesian Nursing Journal, 2025)
Background: Anxiety is a common psychological complication among Diabetes Mellitus (DM) patients, influencing their glycemic control. Stress-related hormones like cortisol and adrenaline, elevated during anxiety episodes, can disrupt glucose metabolism, contributing to hyperglycemia. Purpose: This study investigates the relationship between anxiety levels and blood glucose control in DM patients at Labuang Baji Hospital, Makassar. Methods: A cross-sectional study was conducted with 130 DM patients selected through purposive sampling. Anxiety levels were assessed using the Hamilton Anxiety Rating Scale (HARS), while glycemic control was measured using HbA1c. Descriptive statistics summarized the demographic data, and Pearson correlation analysis evaluated the relationship between anxiety and blood glucose levels. Results: The sample comprised predominantly females (55.4%), with 42.3% aged between 31–50 years. The mean anxiety score was 24.5 (±8.6), while the mean HbA1c level was 8.2% (±1.4). A statistically significant positive correlation (r = 0.45, p < 0.01) was found between anxiety levels and HbA1c, indicating that higher anxiety corresponds with poorer glycemic control. Conclusion: The findings emphasize the significant influence of anxiety on blood glucose levels in DM patients. Addressing anxiety through integrated psychological and medical interventions could improve glycemic outcomes. Holistic DM management strategies should include anxiety reduction techniques to enhance overall health and reduce complications.